Administering the routine activities domain of the Oxford Participation and Activities Questionnaire as a stand-alone scale: the Oxford Routine Activities Measure - Morley, D; Dummett, S; Kelly, L; Jenkinson, C (Dove Medical Press, 2018)
Background: The recently validated Oxford Participation and Activities Questionnaire (Ox-PAQ) is a 23-item patient-reported outcome measure, theoretically grounded in the World Health Organization International Classification of Functioning, Disability and Health. The measure is specifically designed to assess participation and activity in people experiencing a range of health conditions. Initial validation of the Ox-PAQ identified three domains: Routine Activities (14 items), Emotional Well-Being (5 items), and Social Engagement (4 items). The purpose of the analysis reported here was to assess whether the Routine Activities domain of Ox-PAQ could be validated for use as a stand-alone measure without compromising its psychometric integrity. Methods: Three hundred and seventy-three patients with a diagnosis of either chronic obstructive pulmonary disease, multiple sclerosis, or Parkinson’s disease were administered the Ox-PAQ in an online survey. The 14 items of the Routine Activities domain of the Ox-PAQ were subject to factor analytic techniques and assessed for reliability and validity. Results: Three hundred and forty-one patients fully completed the survey, a completion rate of 91.4%. The 14 items loaded onto one single factor with an eigenvalue of 9.29 explaining 66.35% of variance. Reliability was confirmed through corrected item-total correlations ranging from 0.880 to 0.594 and a Cronbach’s alpha value of 0.96. Validity was demonstrated through significant differences in scores between the three disease groups assessed. Conclusion: Results indicate that the Ox-PAQ Routine Activities domain can be legitimately adopted as a stand-alone measure, the Oxford Routine Activities Measure, where researchers wish to focus primarily on the activity component of the Ox-PAQ. It should, however, be emphasized that where a full assessment of all areas of activity and participation highlighted as important during the development of the Ox-PAQ is required, all three domains of the full measure should be administered.